Size and Total Factor Productivity Growth in the Malaysian Islamic Banking Industry: A Non-Parametric Malmquist Productivity Index Test - Sufian, F. (Universiti Sains Islam Malaysia, 2024)
By applying the Malmquist Total Factor Productivity Index (MPI), this paper attempts to provide new empirical evidence on the performance of Malaysian Islamic banks over the period of 2001- 2004. Our results suggest that Malaysian Islamic banks productivity have exhibited an inverted U-shaped behaviour during the period of our study. We found that the domestic banks have exhibited higher productivity growth compared to its foreign counterparts. The decomposition of the productivity change index suggests that Malaysian Islamic banks productivity progress was mainly attributable to technological change rather than efficiency change during the early years, while the opposite was true during the latter year. Further decomposition of the efficiency change index into its pure technical and scale efficiency components suggest that, pure technical efficiency has largely resulted in Malaysian Islamic banks efficiency increase. Our results indicate that while the majority of Malaysian Islamic banks experiencing productivity progress due to technological process came from the medium banks group, on the other hand, the majority of Malaysian Islamic banks that experienced productivity regress due to technological regress came from the small banks group.